2017
DOI: 10.1167/iovs.17-22812
|View full text |Cite
|
Sign up to set email alerts
|

Intraday Repeatability of Bruch's Membrane Opening-Based Neuroretinal Rim Measurements

Abstract: Assessment of BMO-MRW by SD-OCT shows high intraday repeatability, which is comparable to the parameter RNFL thickness. Variability seems not to be driven by typical moderate intraday fluctuations of IOP. The two-dimensional parameter BMO-MRA incorporates a fairly higher intraindividual variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Various authors have indicated the utility of BMO-MRW in diagnosing glaucoma in moderate myopic eyes [8] or small optic discs [9]. BMO-MRW also showed high intraday repeatability, similar to the RNFL thickness parameters, and independence from intraindividual intraocular pressure (IOP) changes [10].…”
Section: Introductionmentioning
confidence: 97%
“…Various authors have indicated the utility of BMO-MRW in diagnosing glaucoma in moderate myopic eyes [8] or small optic discs [9]. BMO-MRW also showed high intraday repeatability, similar to the RNFL thickness parameters, and independence from intraindividual intraocular pressure (IOP) changes [10].…”
Section: Introductionmentioning
confidence: 97%
“…Simply because the actual value of BMO-MRW is greater than that of RNFL, it does not necessarily indicate that values of BMO-MRW are more variable than values of RNFL. Previous studies have revealed that BMO-MRW offers excellent intra-and interobserver reproducibility and intraday repeatability [30][31][32]. The thicker the measurement tissue is, the more there is left to measure over time.…”
Section: Discussionmentioning
confidence: 99%
“…For subjects with either glaucoma or ocular hypertension, mean baseline BMO‐MRW and SD were estimated to 206 and 86 μ m, respectively (Enders et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available automated algorithms are still under development. Manual review and correction is still required (Enders et al 2017;Park et al 2017;Reis et al 2017;Schrems-Hoesl et al 2018;Tun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation